The Analysis Factor Influence Quality of Life Erderly People in Lemper Pamekasan City - Sulistiani Sulistiani (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Based on the data from WHO in 2015, incident of low birth weight in Indonesia is still high. As many as 15,5% of babies born in Malang district. in 2018, total babies born were 38.421 and 1261 babies were born with low birth weight (BPS Kab. Malang). Meanwhile in puskesmas dau, there were 30 babies birth with low birth weight. Factors that can influence LBW include maternal weight before pregnancy, maternal weight during pregnancy, arm circumference, alcohol consumption, cigarette use, symptoms of depression or anxiety and eating pattern. This study is a descriptive study with a linear regression analysis design multiple analysis to analyze physical, psychological, and dietary factors in tribulan III pregnant women against LBW events at Puskesmas Dau. Samples were taken by simple random sampling method with a total of 175 pregnant women. The result shows that these three factors had a significant influence on LBW events with a t-count of 2,200 physical condition factors, a t-count of 8,165 psychologic factors, and a t-count of 3,612 eating conditions. Based on the result of this study, it can conclude that there is significant effect between physical factor, psychological factor and eating pattern to low birth weight event in Puskesmas Dau. The conclusion of this study shows that psychological factors that have the most significant influence on LBW events when compared with other factors. Suggestions that can be given from researcher to Puskesmas Dau are to maintain and improve services to psychological conditions by always involving families in solving problems so that low birth weight will decrease